(untitled) (Journal of Science and Technology, 2016)
In society today, large amounts of chemicals are routinely’ stored, handled and transported. Some of these are products ready for marketing whereas others are used for military purposes. Not all chemical substances imply risks when released. Risk chemicals are classified according to several different criteria, e.g., range effect, toxicity and chemical stability. The number of people who will be injured following the release of chemicals, and the extent of the damage, will depend on numerous factors. Some factors are the properties of the substance, the size of the discharge, the period during which people are exposed and the length of time that passes between exposure and treatment. Chemicals were used for the first time on a large scale at weapon during the First World War. About 1.3 million people were injured and 100,000 killed by chemical weapons during the first World War. Since then, large quantities of thin rent chemical warfare (059 agents have been produced, stored and dispersed during warfare. This paper describes in a concise form the mechanisms of action and antidotes for the most important CW agents.